Emerging public health risk of seasonal human metapneumovirus infection - Balamurugan Shanmugaraj; Chanjetha Murugan; Ramani Priya Sudalai; Kiruthika Jayaraj (Discover Public Health)
Abstract The respiratory tract infections caused by pathogenic viruses are one of the major public health problems causing significant morbidity and mortality globally. Human metapneumovirus (HMPV) is a respiratory pathogen predominantly affecting young children, the elderly and immunocompromised individuals. It is an RNA virus belongs to the family Pneumoviridae. The recent report of the HMPV outbreak (2024-25) along with the increasing number of cases raised public concerns about the potential for another large-scale epidemic or pandemic similar to coronavirus disease (COVID-19). The health authorities clarified that the outbreak is not connected to a new virus and the HMPV resurgence usually follows a seasonal pattern. It is important to distinguish genuine public health threats and manageable seasonal infection which can prevent unnecessary panic. The public awareness and education about the respiratory pathogens are crucial for effective prevention and control measures. Till now, no approved vaccines or effective treatment is available to treat the infection. Hence, prioritizing funding for the vaccine development and therapeutic research is essential. The routine screening is vital considering the increasing prevalence and potential severity of this infection. Further, strengthening the national policies to build better health systems, investing in research, healthcare infrastructure, training, international cooperation, public education and awareness are necessary to manage future viral outbreaks effectively. This review provides an overview of human metapneumovirus as an emerging public health risk, and emphasizes the importance of timely and accurate information sharing for effective management during public health emergencies.